Analisis Nilai Tambah Produk Olahan Buah Mangrove di Kabupaten Mempawah - Eva Dolorosa; Kristin Oktavia Simanjuntak; Marisi Aritonang (AGRIMOR, 2023)
Mangrove fruit processing is a sustainable use of mangrove plants. Mangrove utilization has been widely carried out by processing it into various food, beverage and health products. The purpose of this study was to see how much added value and the ratio of added value from the processing of mangrove fruit into lunkhead and syrup. The problem is that people mostly sell mangrove fruit in raw form at a price of Rp. 3000/Kg but have a relatively short shelf life, namely the durability of the fruit is only up to 2 days after harvest. The research was conducted in Mempawah district. The method used is descriptive method. The results showed that Mempawah Regency produces lunkhead and syrup from the stages of providing raw materials, cleaning, cutting, filtering, mixing and packaging. The added value of dodol and syrup production in Mempawah district is different, the added value of dodol in Mendalok Village is Rp. 24,540, Sand Village lunkhead Rp. 83,453, Big Mangrove lunkhead Rp. 119,565, Mendalok Village Syrup Rp. 156.167, Sand Village syrup Rp. 416,113, Big Mangrove syrup Rp. 148,754. The added value ratio obtained is high because the added value ratio of all processed mangrove fruit products is > 50%.